Acetylated K676 TGFBIp as a severity diagnostic blood biomarker for SARS-CoV-2 pneumonia - Park, Hee Ho; Kim, Hong Nam; Kim, Hyelim; Yoo, Youngbum; Shin, Hyosoo; Choi, Eun Young; Bae, Jong-Sup; Lee, Wonhwa (AMER ASSOC ADVANCEMENT SCIENCE, 2020)
The outbreak of the highly contagious and deadly severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), also known as coronavirus disease 2019 (COVID-19), has posed a serious threat to public health across the globe, calling for the development of effective diagnostic markers and therapeutics. Here, we report a highly reliable severity diagnostic biomarker, acetylated 676th lysine transforming growth factor-beta-induced protein (TGFBIp K676Ac). TGFBIp K676Ac was consistently elevated in the blood of patients with SARS-CoV-2 pneumonia (n = 113), especially in patients in the intensive care unit (ICU) compared to non-ICU patients. Patients' blood samples showed increased cytokines and lymphopenia, which are exemplary indicators of SARS-CoV-2 pneumonia. Treatment with TGFBIp neutralizing antibodies suppressed the cytokine storm. The increased level of TGFBIp K676Ac in ICU patients suggests the promise of this protein as a reliable severity diagnostic biomarker for severe SARS-CoV-2 disease.
Keywords: COVID-19 PNEUMONIA; CYTOKINE STORM; BETA; ACTIVATION; PROTEIN